Cross national research data: access, legality, ethics and opportunities (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2017)
This workshop, convened collaboratively by the German Data Forum and the UK Data forum, was designed to explore recent developments in both countries with respect to improved research access to administrative data. Presentations would give participants an overview of the techniques being developed in Germany and the UK to provide secure access to person-level data. The workshop would also provide an opportunity for discussion about the changing legal environment for research access to personal data and the ethical issues surrounding such uses. The main topic for discussion would be data infrastructure issues and common concerns relating to access, both within Europe and more widely, in terms of access to and linkage between personal data for research into social, economic, environmental and health matters. The ultimate aim is to ensure ways of accessing and analysing data to shed light on policy effectiveness and efficiency at both national and supranational levels. This event was organised by Tim Holt with Peter Elias (UK Data Forum) and Stefan Bender with Claudia Oellers (German Data Forum). It was jointly funded by the UK Economic and Social Research Council (ESRC) and the German Federal Ministry of Education and Research. The agenda for the Workshop can be found at Appendix 1, the list of participants at Appendix 2. A link to the relevant presentation is given after each heading, below. Due to ill health, Eckart Hohmann was unable to attend. Consequently, the session presented by Dr. Francis Crawley and the subsequent discussion was extended. – – Im Dezember 2016 führten das UK Data Forum und der Rat für Sozial- und Wirtschaftsdaten (RatSWD) gemeinsam einen Workshop zum Thema "Cross national research data: access, legality, ethics and opportunities" durch. Ziel des Workshops war der systematische Austausch über aktuelle Entwicklungen beim Forschungszugang zu administrativen Daten in Großbritannien und Deutschland. Die einzelnen Vorträge boten einen Überblick über sichere Zugangswege zu sensiblen personenbezogenen Daten, die in den beiden Ländern entwickelt wurden. Darüber hinaus bot der Workshop eine Plattform, um über Veränderungen der rechtlichen Rahmenbedingungen beim Zugang zu personenbezogenen Forschungsdaten zu diskutieren. Auch forschungsethische Aspekte wurden adressiert. Der Schwerpunkt der Diskussion lag jedoch auf Forschungsdateninfrastrukturen und verbreiteten Herausforderungen beim Datenzugang in Europa. Des Weiteren haben sich die Teilnehmenden über Fragen der Verknüpfbarkeit von personenbezogenen Daten in den Sozial-, Wirtschafts-, Umwelt- und Gesundheitswissenschaften auseinandergesetzt. Es herrschte Einigkeit darüber, dass Zugangswege für die Datenanalyse sichergestellt werden müssen, um die Effektivität und Effizienz politischer Maßnahmen auf nationaler und länderübergreifender Ebene abschätzen zu können. Der Workshop wurde von Tim Holt gemeinsam mit Peter Elias (UK Data Forum) und Stefan Bender gemeinsam mit Claudia Oellers (RatSWD) organisiert. Finanzielle Unterstützung erhielt die Veranstaltung durch das UK Economic and Social Research Council (ESRC) und das Bundesministerium für Bildung und Forschung (BMBF). Das Workshop-Programm findet sich im Anhang 1 (Appendix 1), die Liste der Teilnehmenden in Anhang 2 (Appendix 2). Die Vortragsfolien zu den einzelnen Abschnitten sind verlinkt und können heruntergeladen werden.
Keywords: 330